(untitled) (Research, Society and Development, 2019)
The horticulture is very used in the familiar agriculture in the Brazil, Para state, in which the main part of production is used for family consumption. The lettuce more cultivated is Vanda (Lactuca sativa L.) and the family use own labor. The main objective this paper was evaluable the development of lettuce cv Vanda cultivated in beds with organic compounds and chemistry fertilization (NPK). The radicular system, plant height and production of mass fresh were evaluated. The best results in relation of roots development were in the lettuce cultivated with organic compound in the proportion of 5 kg/m2 due it characteristics as a soil conditioner. The better results in relation fresh mass production and height of plant were obtained with use of chemistry fertilization (NPK), in which this result was obtained mainly by addiction of 10 g/m2 of the extra nitrogen as cover fertilizer. Statistical analyzes showed that difference between height of plant cultivated with chemistry fertilizer and organic compound were similar. In relation of roots development the difference was statistically significant.